Pendampingan Pengelolaan Perpustakaan sebagai Upaya Mewujudkan Sekolah Literat di MI - Fithriyah, Dewi Niswatul (Khidmatuna: Jurnal Pengabdian Masyarakat, 2025)
School libraries play a vital role in supporting the learning process, enhancing students' reading interest, and fostering a culture of literacy. However, at the Madrasah Ibtidaiyah (MI) level, library management still faces several challenges, such as limited book collections, poorly arranged spaces, and low utilization by students and teachers. A mentoring program was carried out to strengthen the library’s role as a school literacy center. The program consisted of three main stages: needs analysis, workshops, and implementation. The analysis phase identified existing problems, the workshop phase provided training for librarians and teachers on library management and digitalization, and the implementation phase focused on reorganizing the space, updating the book collection, and conducting literacy programs. The results showed significant improvements in the competencies of library staff, optimization of library services, and increased student enthusiasm for using the library. The program also encouraged teachers to integrate library use into the learning process. Thus, the mentoring activities effectively strengthened the literacy culture and established the school library as a sustainable learning center in the MI environment.